Surface Modification of Silicone RubberMembrane byMicrowave Discharge to Improve Biocompatibility: Improving biocompatibility of silicone membrane - Sharifian, Mehdi; Hosseini, Seyyed Iman; Shokri, Babak (Iranian Journal of Pharmaceutical Sciences, 2008)
Wetability of biocompatible polymers can be improved by plasma surfacemodification. The purpose of this study was to surface modify an experimental poly(dimethylsiloxane) rubber (PDMS) material in order to improve its wetability andbiocompatibility. Surface properties of the PDMS were characterized using contactangles measurement for wetability analysis. Samples of experimental siliconerubber were surface modified by first argon, hydrogen, oxygen plasma treatment.In all cases, contact angles were measured. We have observed that oxygen, argon,and hydrogen glow discharges are quite effective in reducing the water contact angleof PDMS. However, indifferently to the efficiency of the treatment, practically allof the modified surfaces recovered great part of their original hydrophobicity.Surface modified materials had comparable contact angles to surfactant modifiedsilicone rubber, all being significantly lower than the unmodified material. Oxygenmicrowave discharge treatment proved an effective way of improving the wetabilityand biocompatibility of an experimental silicone rubber without altering bulkproperties.